A potential exodus: what is behind dropping out intentions among university students? - Herrera, Dora; Matos, Lennia; Gargurevich, Rafael; Gómez, Marjhori; Lira, Benjamín; Ferreyra, Cecilia (Frontiers in Education, 2025)
IntroductionThe alarming dropout rates among university students in Peru deplete the country’s human resources and reduce prospects for personal growth and societal development. Explaining those rates calls for a comprehensive and holistic approach beyond the students’ socio-economic characteristics. This study seeks to identify the socio-demographic, academic and psychological variables that predict dropout intention among university students in Peru.Materials and methodThe sample was composed of 768 students from nine universities, both public and private, across the coastal, highland and rainforest regions of Peru. Students completed questionnaires assessing factors that favor resilience, future orientation, and dropout intention.ResultsAs hypothesized, we found that students who scored higher on factors favoring resilience and future orientation subscales, with the exception of the exploration sub-dimension, were less likely to develop dropout intentions. We found differences by sex and type of university; then evaluated whether the model parameters varied by sex. Our findings show higher dropout intentions among male students. No significant relationships were found between grades, tutoring programme and future orientation.DiscussionResults contribute to support these university students as valuable human resources who, due to Peru’s characteristics, lack easy access to higher education and should be protected. Our findings also provide general guidelines for further interventions to counter the risk of increased dropout rates at the university level.